2020
DOI: 10.17706/jsw.15.3.68-73
|View full text |Cite
|
Sign up to set email alerts
|

Chatbot Based Solution for Supporting Software Incident Management Process

Abstract: A sét of stéps for impléménting a chatbot, to support décision-making activitiés in thé softwaré incidént managémént procéss is proposéd and discusséd in this articlé. Each stép is préséntéd indépéndéntly of thé platform uséd for thé construction of chatbots and aré détailéd with théir réspéctivé activitiés. Thé proposéd stéps can bé carriéd out in a continuous and adaptablé way, favoring thé constant training of a chatbot and allowing thé incréasingly cohésivé intérprétation of thé inténtions of thé spécialis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…State-of-the-art AI and Natural Language Processing (NLP)-boosted conversational assistants can automatically sustain dialogues with end users [ 9 , 10 , 11 ]. Nowadays, chatbots are commonly applied to management [ 12 , 13 , 14 ], education [ 15 , 16 , 17 ] and healthcare [ 18 , 19 , 20 ]. It has been demonstrated that they perform better when designed on purpose for specific domains and user groups, and when their utterances are short and accurate within those domains.…”
Section: Related Workmentioning
confidence: 99%
“…State-of-the-art AI and Natural Language Processing (NLP)-boosted conversational assistants can automatically sustain dialogues with end users [ 9 , 10 , 11 ]. Nowadays, chatbots are commonly applied to management [ 12 , 13 , 14 ], education [ 15 , 16 , 17 ] and healthcare [ 18 , 19 , 20 ]. It has been demonstrated that they perform better when designed on purpose for specific domains and user groups, and when their utterances are short and accurate within those domains.…”
Section: Related Workmentioning
confidence: 99%